DETECTION OF FRAUD INDICATIONS IN FINANCIAL STATEMENTS USING FINANCIAL SHENANIGANS - Eklamsia Sakti; Tarjo Tarjo; Prasetyono Prasetyono; Moh. Riskiyadi (Asia Pacific Fraud Journal, 2020)
This study aims to empirically test the detection of indications of financial statement fraud based on financial shenanigans. Financial shenanigans are proxied by the growth in days' sales outstanding, cash flow from operating divided by net income, and accounts receivable divided by sales. Indication of financial statement fraud is proxied by the F-Score model. This research was conducted at oil and gas companies in Indonesia and Malaysia. Hypothesis testing used multiple linear regression analysis. The test was carried out in three steps, namely testing on Indonesia and Malaysia, Indonesia, and Malaysia. The results of this study found evidence that the growth of the days' sales outstanding is significant to the indication of financial statement fraud in Malaysia. Another result is that the growth in a collection period, cash flow from operating divided by net income, and accounts receivable divided by sales is not significant if tested separately for Indonesia and Malaysia and Indonesia.